Ecological and Ethnobotanical Study of Myrtus communis L. (Myrtaceae) in Al-Jabal Al-Akhdar, Libya (Libyan Journal of Ecological & Environmental Sciences and Technology, 2021)
The Myrtle (Myrtus communis) is a common shrub widespread in the Mediterranean. Its fruit and leaves have antioxidant, antibacterial and antifungal properties, and are used for their content of essential oils; however, most commonly used is as an ingredient in locally made juice. The uncontrolled exploitation of Myrtle has reduced both the species geographical coverage and the size of individual populations. This study was selected to investigate the ethnobotanical of M. communis and to identify the main reasons for their folk uses, methods of uses and their geographical distribution in the Al Jabal Al Akhdar area, Libya. Also, an experiment was carried out to determine the allelopathic, as an ecological process in regulating plant population in ecosystems, the potential of plant parts by which may other plants be affected. Such volatile substances released from Myrtle leaves for controlled cultivation requires a characterization present both within and between populations. The use of Myrtle as a flavouring agent and stomachic is 90% and 10.9%, respectively. The plant use was also recorded for Diabetes (60%), Anti-septic, Blood purification and Constipation (6.6%). Our results of allelopathic on germination and growth bioassay experiment demonstrated that germination percentage of Hordeum vulgare and Triticum aestivum (Recipient Species) was significant (P ≤ 0.05). The germination percentage decreased with the increase in Myrtus communis Leaves Aqueous Extract (MCLAE) concentration. Shoot Length, Root Length also decreased with the increase in the extract concentration, whereas the reverse was true for Seedling Dry Weight increased with the increase of MCLAE concentration
Keywords: Ethnobotanical; Allelopathic; Myrtus communis; Recipient species